ZnO Nanoparticle-Assisted Synthesis of Thiazolo[3,2-α]Pyrimidine Analogs: Antibacterial and Antioxidant Activity, In Silico Molecular Docking, and ADMET Prediction Study - Demis Zelelew; Milkyas Endale; Yadessa Melaku; Taye B. Demissie; Japheth O. Ombito; Rajalakshmanan Eswaramoorthy (Journal of Chemistry)
In the present study, a new series of nine Thiazolo[3,2-α] pyrimidine analogs were synthesized in good to excellent yields (87.9–96.9%) and improved reaction time using a ZnO nanoparticle-assisted protocol. All the synthesized compounds were characterized using a combination of physicochemical parameters, UV-visible, 1H-NMR, and 13C-NMR spectroscopic methods. Among the synthesized compounds, the in vitro antibacterial activity displayed by compound 16 was higher (14.67 ± 0.58 mm at 500 μg/mL) against P. aeruginosa compared to amoxicillin (12.33 ± 0.58 mm at 500 μg/mL), whereas compounds 14 and 18 showed comparable activity (12.00 ± 0.00 mm and 12.33 ± 0.58 mm at 500 μg/mL and 250 μg/mL, respectively) against the same strain. The activities displayed by compounds 14, 16, 18, and 20 were comparable (12.33 ± 1.15 mm, 12.65 ± 0.58 mm, 12.33 ± 0.58 mm, and 12.00 ± 1.00 mm, respectively, at 500 μg/mL) to amoxicillin (13.33 ± 1.15 mm at the same concentration) against E. coli. Compound 19 showed good activity (12.00 ± 1.72 mm at 500 μg/mL) against S. aureus compared to amoxicillin (16.33 ± 0.58 mm at the same concentration). Compound 19 displayed the highest percent inhibition of DPPH with an IC50 value of 9.48 g/mL using the DPPH free radical scavenging assay compared to ascorbic acid (3.21 g/mL) and promising inhibition of peroxide formation (76.28 ± 0.12%), demonstrating its potential in preventing the formation of lipid peroxides. Thus, according to our findings, both the biological activities and in silico computational results revealed that compounds 14, 16, and 18 are good antibacterial agents against P. aeruginosa and E. coli, whereas compound 19 was found to be a promising antibacterial agent against S. aureus and an antioxidant agent. The present study revealed that the synthesized compounds appear to be lead compounds for rational drug design.